Some Results on mX-N-connected Space - Salih, Ahmed A.; Ali, Haider J. (Iraqi Journal of Science, 2021)
In this essay, we utilize m - space to specify mX-N-connected, mX-N-hyper connected and mX-N-locally connected spaces and some functions by exploiting the intelligible mX-N-open set. Some instances and outcomes have been granted to boost our tasks.